NADPH phagocyte oxidase knockout mice control Trypanosoma cruzi proliferation, but develop circulatory collapse and succumb to infection. - Helton C Santiago; Claudia Z Gonzalez Lombana; Juan P Macedo; Lara Utsch; Wagner L Tafuri; Maria José Campagnole-Santos; Rosana O Alves; José C F Alves-Filho; Alvaro J Romanha; Fernando Queiroz Cunha; Mauro M Teixeira; Rafael Radi; et al. (Public Library of Science (PLoS), 2012)
(•)NO is considered to be a key macrophage-derived cytotoxic effector during Trypanosoma cruzi infection. On the other hand, the microbicidal properties of reactive oxygen species (ROS) are well recognized, but little importance has been attributed to them during in vivo infection with T. cruzi. In order to investigate the role of ROS in T. cruzi infection, mice deficient in NADPH phagocyte oxidase (gp91(phox) (-/-) or phox KO) were infected with Y strain of T. cruzi and the course of infection was followed. phox KO mice had similar parasitemia, similar tissue parasitism and similar levels of IFN-γ and TNF in serum and spleen cell culture supernatants, when compared to wild-type controls. However, all phox KO mice succumbed to infection between day 15 and 21 after inoculation with the parasite, while 60% of wild-type mice were alive 50 days after infection. Further investigation demonstrated increased serum levels of nitrite and nitrate (NOx) at day 15 of infection in phox KO animals, associated with a drop in blood pressure. Treatment with a NOS2 inhibitor corrected the blood pressure, implicating NOS2 in this phenomenon. We postulate that superoxide reacts with (•)NO in vivo, preventing blood pressure drops in wild type mice. Hence, whilst superoxide from phagocytes did not play a critical role in parasite control in the phox KO animals, its production would have an important protective effect against blood pressure decline during infection with T. cruzi.